1997
DOI: 10.1152/jappl.1997.82.4.1290
|View full text |Cite
|
Sign up to set email alerts
|

Determination of production of nitric oxide by lower airways of humans—theory

Abstract: Exercise and inflammatory lung disorders such as asthma and acute lung injury increase exhaled nitric oxide (NO). This finding is interpreted as a rise in production of NO by the lungs (VNO) but fails to take into account the diffusing capacity for NO (DNO) that carries NO into the pulmonary capillary blood. We have derived equations to measure VNO from the following rates, which determine NO tension in the lungs (PL) at any moment from 1) production (VNO); 2) diffusion, where DNO(PL) = rate of removal by lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 27 publications
2
69
0
Order By: Relevance
“…Thus, both haemodynamic alteration and hyperventilation have been suggested as being important stimuli for NO-production during exercise [15,18,19]. Moreover, it has been suggested recently that exercise does not necessarily increase V 'NO but only shifts the elimination of a proportion of the V 'NO from the blood to the airways, less NO diffusing into the blood and more being removed by ventilation [20]. In our study, the identical V 'O 2 values measured at -10 and 22°C at rest and during exercise shows an identical metabolic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both haemodynamic alteration and hyperventilation have been suggested as being important stimuli for NO-production during exercise [15,18,19]. Moreover, it has been suggested recently that exercise does not necessarily increase V 'NO but only shifts the elimination of a proportion of the V 'NO from the blood to the airways, less NO diffusing into the blood and more being removed by ventilation [20]. In our study, the identical V 'O 2 values measured at -10 and 22°C at rest and during exercise shows an identical metabolic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…gas exchange; model; exhaled breath NITRIC OXIDE (NO) performs many important functions in the lungs and has been regarded as a potential noninvasive marker of lung inflammation (2). The characteristics of NO gas exchange are unique compared with other endogenous gases because exhaled NO is thought to have a significant alveolar and airway source (6,8,15,22). A two-compartment model is commonly used to characterize NO exchange dynamics for healthy and diseased lungs (9,11,13,20,21,23,24,27,29), by partitioning exhaled NO into airway and alveolar contributions using three flow-independent NO exchange parameters: maximum flux of NO from the airways (JЈaw NO ), the diffusing capacity of NO in the airways (Daw NO ), and the steady-state alveolar concentration (CA NO ).…”
mentioning
confidence: 99%
“…End tidal NO value was stable over many breaths and much easier to identify. When necessary, changes in minute ventilation, which can affect exhaled NO concentration, can be accounted for by calculating NO production [25]. The effect of nasal contamination [26] on NOet measurement is likely to be very small during normal breathing because most of the NO would have been washed away early during expiration, and can be further minimized by applying a small negative pressure at the nose [27].…”
Section: Discussionmentioning
confidence: 99%
“…Based on such evidence, it is reasonable to suggest that NOet represents alveolar NO and any changes in exhaled NO may reflect changes in NO diffusing into the blood. Indeed Hyde et al [25] suggested that changes in NO in the exhaled gas represents changes in diffusing capacity rather than changes in NO production in the airways. Clini et al [40] came to similar conclusions.…”
Section: Discussionmentioning
confidence: 99%